Indoors and health: results of a systematic literature review assessing the potential health effects of living in basements - Mezzoiuso, Angelo Giosué; Gola, Marco; Rebecchi, Andrea; Riccò, Matteo; Capolongo, Stefano; Buffoli, Maddalena; Tirani, Marcello; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2017)
A new law approved in March 2017 in the Lombardy Region makes it possible to live in basements. Basements are defined as buildings partly below curb level but with at least one-half of its height above the curb. Basements’ features and structural characteristics might pose risks to human health. In this paper we adopt a multidisciplinary approach to assess the potential health effects of living in basements. In particular, we define a conceptual framework to describe basements’ structural characteristics which are risk factors, as well as the mechanisms through which they impact on human health. We also conduct a systematic review on the scientific databases PubMed,Embase, DOAJ, Proquest and EBSCO to retrieve, pool and critically analyze all available research that quantified the risk of living in basements for different health outcomes. Available evidence suggests living in basements increases the risk of respiratory diseases (asthma and allergic disorders); more heterogeneous data are available for cancers and cardiovascular diseases. As more quantitative data need to be prospectively retrieved to assess and monitor the risk of living in basements for human health, clear minimum requirements for light, air, sanitation and egress are to be defined by technical experts and enforced by policy makers.